(3JMQjQ cJGH GdefGXQ dChbdjOSs - (3KGHJ Hf obnqQI Hf RgQhf GdMQGfj GdUGHF, CHh GdMSf, J (B288 (3g` s; (3GbdjOSs ((3YHOGdcGai Hf YHOGdeLjO GdJHQjRi s)
(3ChdgG (B:s
(3UOQ GdcJGH GdYjf JMOK HSJeQGQ ef GdCLSGe dfHQI ai GdLSe GdTGa GdeJhSW HjfgeG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3EUdGMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B35 s
Keywords: (3GdQjGVjGJs